2014
DOI: 10.1186/s13054-014-0668-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pseudomonas aeruginosa type III secretion, antibiotic resistance, and clinical outcome: a review

Abstract: Pseudomonas aeruginosa uses a complex type III secretion system to inject the toxins ExoS, ExoT, ExoU, and ExoY into the cytosol of target eukaryotic cells. This system is regulated by the exoenzyme S regulon and includes the transcriptional activator ExsA. Of the four toxins, ExoU is characterized as the major virulence factor responsible for alveolar epithelial injury in patients with P. aeruginosa pneumonia. Virulent strains of P. aeruginosa possess the exoU gene, whereas non-virulent strains lack this part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 99 publications
(108 reference statements)
2
104
2
2
Order By: Relevance
“…However, transcript levels of algC were similar between these two PA14 strains (Supplementary information, Figure S2A). We then assessed transcript levels of several virulence factors and virulence-associated factors that are known to be injected via the type 3 secretion system (T3SS) into host cells to facilitate invasion [16,17]. We found that mRNA levels of T3SS exoenzymes ExoT, ExoU and ExoY and virulence-associated factors LasR, LasI, RhlR, RhlI and RpoS were all significantly increased in PA14 ∆TCR mutant compared with those in WT strain, and the increase was reversed in the ∆TCR strain complemented with CRISPR-Cas system (named the complemented strain hereafter; Figure 1B and Supplementary information, Figure S2A).…”
Section: Pa14 Crispr-cas Is Necessary For Lasr Mrna Repressionmentioning
confidence: 99%
“…However, transcript levels of algC were similar between these two PA14 strains (Supplementary information, Figure S2A). We then assessed transcript levels of several virulence factors and virulence-associated factors that are known to be injected via the type 3 secretion system (T3SS) into host cells to facilitate invasion [16,17]. We found that mRNA levels of T3SS exoenzymes ExoT, ExoU and ExoY and virulence-associated factors LasR, LasI, RhlR, RhlI and RpoS were all significantly increased in PA14 ∆TCR mutant compared with those in WT strain, and the increase was reversed in the ∆TCR strain complemented with CRISPR-Cas system (named the complemented strain hereafter; Figure 1B and Supplementary information, Figure S2A).…”
Section: Pa14 Crispr-cas Is Necessary For Lasr Mrna Repressionmentioning
confidence: 99%
“…[3][4][5] P. aeruginosa clinical isolates are often resistant to most b-lactams and fluoroquinolones and, sometimes, resistant to aminoglycosides, such as gentamicin and amikacin, thus categorizing them as multi-drug resistant P. aeruginosa (MDRP). 4,[6][7][8][9] Limitations in the number of effective antimicrobial agents for treating MDRP infections leads to the high mortality rates associated with the acute lung injury induced by this bacterium. 5 While seeking new prophylactic or therapeutic strategies that do not rely on conventional antimicrobial agents, we have investigated the use of an immunotherapy approach that targets the P. aeruginosa type III secretion system.…”
Section: Introductionmentioning
confidence: 99%
“…The existence many of agents in P. aeruginosa leads to intrinsic resistance to many antimicrobials including bacterium's outer membrane barrier, the presence of multi drug efflux trans-porters and endogenous antimicrobial inactivation. The all of this agents, also inappropriate chemotherapy and lagging in antibiotic discovery was caused "antibiotic resistance crisis" (6,9). The previous studies were showed that the inappropriate chemotherapy leads to emerge of the multi-drug resistant isolates (10), especially in burn patients, the rate of resistance to most of antibiotics for P. aeruginosa isolated was reported higher than 70% (11), However, the ExoU + isolates are more resistance to floroquinolons (12).…”
Section: Introductionmentioning
confidence: 99%
“…The type III secretion system (TTSS) has been known to be a major virulence, which is determined in pathogenesis of acute infection, bacteremia, sepsis and subsequent mortality. The TTSS allows the injection of toxins into the cytosol of target eukaryotic cells, where they destroy host cell defense and signaling systems and that subsequently rapid call necrosis or modulating the actin cytoskeleton (4)(5)(6). Four effector proteins have been identified: ExoU, which is a phospholipase and it has been characterized as a major virulence factor in acute lung injury, ExoY that is an adenylate cyclase, and ExoS and ExoT which are bifunctional proteins (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation